Penanaman Nilai Cinta Tanah Air Di Sekolah(Studi Kasus Siswa Kelas VII SMP Negeri 2 Colomadu Kabupaten Karanganyar Tahun Ajaran 2014/2015) - Hartika, Dwi (2016)
The low values of patriotism which is owned by learners should immediately get treatment from the school, especially the teachers. This study aimed to describe the planting of value patriotism in the seventh grade students in Junior High School 2 Colomadu the school year 2014/2015 and describe forms of cultivation value of patriotism in the seventh grade students in Junior High School 2 Colomadu the school year 2014/2015. This is where the research SMP Negeri 2 Colomadu Karanganyar the school year 2014/2015. This research is a qualitative descriptive study using a case study approach. Subjects in this study were principals, teachers, and students of class VII SMP Negeri 2 Colomadu Karanganyar academic year 2014/2015, while the object of this research is an investment value of patriotism in the seventh grade students of SMP Negeri 2 Colomadu Karanganyar Academic Year 2014/2015. The results showed that planting of value patriotism in Class VII in SMP Negeri 2 Colomadu done through the concept of internalizing the values of patriotism in the subject, namely: 1) Using the Indonesian language is good and true, carried out through the delivery of Lessons by Using Indonesian and wall hangings are taught to use the Indonesian well and correctly; 2) Love the national culture, carried through the memorial ceremony HUT RI, Extracurricular Activities Scouts. OSIS Ekstrakurikulier activities as well as activities Ekstrakurikluer Traditional Dance; 3) Liking made in Indonesia, conducted by Mutual Cooperation Friday activities Net and use batik as an Indonesian traditional clothing. Constraints in Love Homeland Investment Value in Class VII in SMP Negeri 2 Colomadu 2014/2015 academic year is in the planning is still limited knowledge of teachers about planting the value of patriotism, especially in the preparation of learning tools; occurs due to environmental differences between the school environment and the family environment is also becoming an obstacle as well as the absence of a clear concept in the evaluation related to the planting of values patriotism make teachers in SMPN 2 Colomadu confused.